Effect of Sechium edule var. nigrum spinosum (Chayote) on Oxidative Stress and Pro-Inflammatory Markers in Older Adults with Metabolic Syndrome: An Exploratory Study - Rosado-Pérez, Juana (Antioxidants (Basel), 2019)
Metabolic syndrome (MetS) is a risk factor for cognitive deterioration and frailty in older adults. In this regard it has been shown that oxidative stress (OxS) and chronic inflammation are involved in the pathophysiology of these alterations. Harmless antioxidant and anti-inflammatory therapeutic alternatives have been proposed, such as the consumption of Sechium edule (chayote), but the evidence is inconclusive. For this reason, an exploratory study of a single group chosen by convenience sampling, including 12 older adults, with an average age of 71 ± 6 years (10 women and 2 men) with a diagnosis of MetS according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP/ATP III) criteria. This exploratory study aimed to determine the effect of the consumption of the dried fruit powder supplement of Sechium edule var. nigrum spinosum (500 mg, 3 times per day) for six weeks on the markers of OxS in elderly adults with MetS. All participants’ OxS markers were measured before and after treatment. There was a statistically significant decrease in the concentration of lipoperoxides (baseline, 0.289 ± 0.04 vs. post-treatment, 0.234 ± 0.06 μmol/L, p < 0.05), together with a significant increase in total antioxidant status (baseline, 0.97 ± 0.18 vs. post-treatment, 1.2 ± 0.12 mmol/L, p < 0.05). In this sense, the oxidative stress index showed a statistically significant decrease (baseline, 1.7 ± 0.78 vs. post-treatment, 0.75 ± 0.87, p < 0.05). A statistically significant decrease in the concentration of TNF-α after treatment was also found (baseline, 5.3 ± 1.4 vs. post-treatment, 3.5 ± 1.3, p < 0.05).Our findings suggest that the consumption of the dry fruit of Sechium edule has an antioxidant and anti-inflammatory effect in older adults with metabolic syndrome.